Fundamentals of entrepreneurship (ENT300) : Borneo Steamboat and Grill / Evelyn Syungkir … [et al.] - Syungkir, Evelyn; Timbang, Gabriela; Ingkai, Jenner Blu; David, Edmund Langgan (2014)
Our business is called Borneo Steamboat and Grill, which we dedicated to those steamboat and grill food lovers. The business is formed under the Business Registration Act 1956 (Amendment 1978) and Procedures of Business Registration 1957 where we form a partnership. The company is commencing on the 1 st of January 2014 and it is located at the Jalan Taman Huising, Kuching.